Starch-based completely biodegradable polymer materials (eXPRESS Polymer Letters, 2009)
Starch is a natural polymer which possesses many unique properties and some shortcoming simultaneously. Some synthetic polymers are biodegradable and can be tailor-made easily. Therefore, by combining the individual advantages of starch and synthetic polymers, starch-based completely biodegradable polymers (SCBP) are potential for applications in biomedical and environmental fields. Therefore it received great attention and was extensively investigated. In this paper, the structure and characteristics of starch and some synthetic degradable polymers are briefly introduced. Then, the recent progress about the preparation of SCBP via physical blending and chemical modification is reviewed and discussed. At last, some examples have been presented to elucidate that SCBP are promising materials for various applications and their development is a good solution for reducing the consumption of petroleum resources and environmental problem.